2011
DOI: 10.1111/j.1863-2378.2010.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin‐Resistant Staphylococcus aureus (MRSA) in Three Dairy Herds in Southwest Germany

Abstract: The objective of this study was to analyse the occurrence of methicillin-resistant Staphylococcus aureus (MRSA) in three dairy herds in the southwest of Germany that had experienced individual cases of clinical and subclinical mastitis associated with MRSA. The herds were identified by the detection of MRSA during routine resistance testing of mastitis pathogens. All quarters of all cows in the herds that were positive on California Mastitis Test were sampled for bacteriological analysis on two occasions. Bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
3
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 26 publications
(34 reference statements)
5
107
3
5
Order By: Relevance
“…FT-IR allowed for rapid species identification of S. aureus isolates (Spohr et al, 2011). For this purpose, bacterial isolates were cultivated on sheep blood agar plates (Oxoid) at 37°C for 24 h. Sample preparation, FT-IR spectroscopy (using IFS 28/B spectrometer, BrukerOptics, Ettlingen, Germany) and data acquisition were performed as described previously (Kuhm et al, 2009).…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
See 1 more Smart Citation
“…FT-IR allowed for rapid species identification of S. aureus isolates (Spohr et al, 2011). For this purpose, bacterial isolates were cultivated on sheep blood agar plates (Oxoid) at 37°C for 24 h. Sample preparation, FT-IR spectroscopy (using IFS 28/B spectrometer, BrukerOptics, Ettlingen, Germany) and data acquisition were performed as described previously (Kuhm et al, 2009).…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…4.2, BrukerOptics) and an artificial neural network built by the NeuroDeveloper software (Synthon, Heidelberg, Germany). The differentiation of S. aureus was performed with a method described previously (Spohr et al, 2011).…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…Spohr et al (2011) found MRSA in 5 out of 7 cows and in 4 out of 7 calves from nasal swabs in Germany. Huber et al (2010) reported 3 MRSA isolates from nasal swabs of 300 calves.…”
Section: Identification Of Mrsamentioning
confidence: 99%
“…S. aureus inoculum is prepared by diluting 0.5 McFarland equivalent suspension of a strain with sterile normal saline to the concentration of 104 CFU/ml. The plates are spot inoculated and incubated at 35 °C for 24 h. An oxacillin MIC of less than or equal to 2 μg/ml is indicative of susceptible and that of > 2 μg/ml resistant (CLSI, 2007 (Spohr et al, 2011) and0.4% in Hungary (Juhasz-Kaszanyitzky, 2007). In a recent study by Paterson et al (2012) (Makovec and Ruegg, 2003) and 4% in Minnesota (Haran et al, 2012) has been reported.…”
Section: Identification Of Mrsamentioning
confidence: 99%
“…Recently, another group of LA-MRSA strains (CC130, CC425, and CC1943) that were initially thought to be bovine-speciic lineages emerged in humans [101]. A number of multidrugresistant MRSA were isolated from bovine mastitis in Germany [97,102], the majority of which were MRSA ST398 related to animal strains, but an isolate of the clonal complex group CC8 was identiied as a human epidemic MRSA strain Irish-01 [103]. In 2010, Hata et al irst discovered MRSA in cow's milk in Japan and the genotypes (ST5-SCCmec II) were the same as or similar to human strains [104].…”
Section: Introductionmentioning
confidence: 99%